Application of Trypan Blue Stain in the Microbiological Diagnosis of Infectious Keratitis—A Case Series. Issue 12 (December 2021) - Sharma, Supriya; Rathi, Varsha M.; Murthy, Somasheila I.; Garg, Prashant; Sharma, Savitri
Abstract : Purpose: The purpose of this study was to report 3 cases of microbial keratitis, wherein trypan blue staining was used to aid the microbiological diagnosis of fungal keratitis and Pythium keratitis in a rural setup. Methods: Three consecutive patients who presented with a diagnosis of infectious keratitis underwent corneal scraping, and the smears were assessed using trypan blue stain and potassium hydroxide (KOH) mount. Results: Of the 3 cases, the first 2 cases showed septate fungal filaments in trypan blue–stained preparation and KOH mount. Case 3 showed the presence of broad aseptate filaments with ribbon-like folds on both KOH mount and trypan blue stain, consistent with the diagnosis of Pythium keratitis. The first 2 cases improved with topical and systemic antifungals. Case 1 healed with scarring at 7 weeks with improvement in best-corrected visual acuity (BCVA) to 20/60. Case 2 healed within 2 weeks, and BCVA improved to 20/40. Case 3 received topical linezolid (0.2%), azithromycin eye ointment, and oral azithromycin. At 5 weeks the infection decreased but thinning was noted, which necessitated tissue adhesive and bandage contact lens application. Scarring was noted at 10 weeks, and BCVA improved to 20/40. Conclusions: In this case series, trypan blue staining showed promising results in the easy identification of aseptate and septate fungal elements. This is the first case series showing the utility of this stain in the management of microbial keratitis.